Wpływ judaizmu na prawodawstwo Izraela - Pohl, Artur (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
Despite the fact that Israel strives to be perceived as a modern state, it is characterized by very high impact of ultra-orthodox groups on its legal system. The lack of separation between the religion and the state causes many tensions and pathologies within the state’s system. Wide range of rights, which have been given to the ultra-orthodoxies since the establishment of Israel, led to the co-existence of two legal systems – religious and secular one, and to the privileged position of Haredi in society. It is manifested in such spheres like: citizenship, marriage, divorce, adoption, military service or the restrictions of business activity during the Sabbath. The aim of the article is to analyze the impact of Judaism on the legal system of Israel and also the implications of the last parliamentary elections.